“Tatiana’s Dream” in the Spanish Version of the Verse Novel Eugenio Oneguin - Razumóvskaya, Veronica A. (Mundo Eslavo, 2013)
This article offers a critical study of the Spanish translation of a fragment from A. Pushkin’s verse novel Eugenio Oneguin entitled “El sueño de Tatiana” (“Tatiana’s dream”).